Acceptance of donor eggs, donor sperms, or donor embryos in Indian infertile couples - Kaberi Banerjee; Bhavana Singla (Wolters Kluwer Medknow Publications, 2018)
Context: The reduction or loss of natural fertility is deeply painful in couples that are considering the use of donor gametes or donor embryos. This is the first study to assess the acceptability of donor gametes or embryos in Indian population. Aim: The aim of the study was to assess the attitude toward egg, sperm, and embryo donation among Indian the infertile couples. Settings: This study was conducted at infertility outpatient clinic New Delhi. Design: This study was a cross-sectional study. Materials and Methods: From October 1, 2015, to December 31, 2015, a total of 594 infertile couples were assessed. A well-structured questionnaire was given to each infertile couple at the first visit. Both female and male partners had filled the questionnaire separately. The acceptance rate of couple toward the egg, sperm, and embryo donation was assessed. Results: Out of 594 female partners, 118 females agreed for donor eggs (19.9%), 116 females agreed for donor sperms (19.5%), and 93 females agreed for donor embryos (15.7%). Out of 594 male partners, 262 males agreed for donor eggs (44.1%), 90 males agreed for donor sperms (15.2%), and 141 males agreed for donor embryos (23.7%). Conclusions: The overall acceptance of donor eggs, sperms, or embryos in Indian infertile couples is low. The acceptance rate of females for donor eggs or donor sperms is same, but males are more amenable to accept donor eggs than donor sperms. This is the first study to assess the acceptability of donor gametes or embryos in Indian population.